The Influence of Norms, Environmental Attitudes, and Perceived Behavioral Control on Plastic Bag Use: A Behavioral-Economic Perspective - Paramananda, Nyoman; Idawati, Ida Ayu Agung; Yamawati, Ni Kadek Sioaji; Putra, I Komang Agus Sedana; Aprianto, Ni Gede (Journal of Applied Business, Taxation and Economics Research, 2025)
Despite local regulations banning their use, single-use plastic bags remain widely consumed in Denpasar City. This study uses the Theory of Planned Behavior (TPB) to explore how subjective norms, environmental attitudes, and perceived behavioral control influence consumer intention and actual behavior, with intention acting as a mediating factor. The results suggest that a sense of control, environmental awareness, and social pressure play important roles in reducing plastic bag usage through behavioral intention. More importantly, the continued reliance on plastic bags imposes real economic costs—ranging from increased public spending on waste management to environmental damage that threatens tourism and fisheries. These hidden costs underline the urgency of combining regulatory measures with behavioral and economic strategies. Policies that support reusable alternatives, provide targeted incentives, and reshape social norms are essential not only for protecting the environment but also for ensuring long-term economic sustainability.